(untitled) (Journal of Business and Technology (Dhaka), 2016)
This research paper is an attempt to estimate the effect of training on employee performance in the telecommunication industry of Bangladesh. This study is conducted mainly based on primary data which were collected from a questionnaire survey encompassing the opinion of 100 employees working currently at six telecommunication companies. A theoretical framework has been formulated to estimate a relationship between training and employee performance, in the presence of intervening variables. Variables examined in this study are: Training (Independent Variable); Job Knowledge, Skill, Positive Attitude (Intervening Variables) and Employee Performance (Dependent Variable). The study revealed that there are positive and statistically significant effects of training on employee performance. The study also discovered that investment on employee training in the telecommunication sector can augment employee performance by enhancing job knowledge, skill and creating positive attitude among employees. Journal of Business and Technology (Dhaka) Vol.10(2) 2015; 67-80